CHARACTERIZATION OF WASTE PET POWDER AS ATOMIZATION PRODUCT - Pamuji, Hari; Alqap, A Sofwan F; Suandi, Agus (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
A nozzle of diameter 25 cm of a closed coupled type was set at an outlet gap 0,05 mm to atomize polyethylene terephthalate plastic wastes. Parameters of pressure and heating temperature were varied into 5 bar, 6 bar and 7 bar pressures, and at 275?C, 285?C and 295?C heating. A vessel to collect the product was 40 cm diametrally away from the nozzle mouth. The products were the form of powders, yarn and liquid. The powders were only 4,77%, 6,45% and 2,94% of each heating temperature aforementioned.